Health Literacy, Perceived Threat, and Posttraumatic Stress Disorder During the COVID-19 Pandemic in Saudi Arabia - Alatawi Y; Alshehri FS; Alhifany AA; Alharbi A; Alghamdi BS (Dove Medical Press, 2020)
Yasser Alatawi,1 Fahad S Alshehri,2 Abdullah A Alhifany,3 Adnan Alharbi,3 Badrah S Alghamdi4 1Department of Pharmacy Practice, Faculty of Pharmacy, University of Tabuk, Tabuk, Saudi Arabia; 2Department of Pharmacology and Toxicology, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 3Department of Clinical Pharmacy, College of Pharmacy, Umm Al-Qura University, Makkah, Saudi Arabia; 4Department of Physiology, Neuroscience Unit, Faculty of Medicine, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Fahad S AlshehriDepartment of Pharmacology and Toxicology, College of Pharmacy, Umm Al‑Qura University, Al‑Abidiyya, Makkah 21955, Kingdom of Saudi ArabiaTel +966 542166571Email fsshehri@uqu.edu.saPurpose: This study aimed to investigate the prevalence of and factors associated with posttraumatic stress disorder (PTSD) during the COVID-19 pandemic in Saudi Arabia.Materials and Methods: This was a cross-sectional online survey that targeted adults over the age of 18 residing in Saudi Arabia. The data collection began June 1, 2020 and continued for four weeks. The Posttraumatic Stress Disorder Checklist-Specific, the Brief Illness Perception Questionnaire version BIP-Q5, and a 9-item health literacy measure were used.Results: There were 1249 participants, of which 62.21% were under the age of 34. The prevalence of PTSD was 19.5% among all participants. The results showed that both the perception of threat (OR =1.17, 95% CI = 1.13− 1.19) and health literacy (OR =0.97, 95% CI = 0.95− 0.99) were associated with PTSD symptoms.Conclusion: This study highlights important findings that the level of an individual’s perception of threat and health literacy is associated with symptoms of PTSD. Thus, an understanding of these constructs in the target population will enable the development of better measures designed to reduce the psychological impact of the COVID-19 pandemic.Keywords: COVID-19, Saudi Arabia, posttraumatic stress disorder, perception, health literacy